Possible Factors Concerning the Crossing of Formosan Ferret-Badger Rabies over the Daan River in Miaoli County, Taiwan - Cheng-Hung Lai; Mei-Chuan Wang; Chia-Ning Hsu; Chun-Yi Chang; Satoshi Inoue; Chang-Young Fei (Animals)
The first detection of Formosan ferret-badger (FFB) rabies on the main island of Taiwan occurred in July 2013. National surveillance reports indicated that prior to 2023, rabies outbreaks were limited to the southern region of the Daan River, which was considered a natural barrier preventing the spread northwards. However, in 2023, four new cases of rabid FFBs emerged in Miaoli County, located north of the Daan River, suggesting that the epizootic had crossed the river. Several factors may have contributed to the ability of reservoir FFBs to cross over the Daan River. Firstly, there was a decrease in rainfall in the upstream area of the Daan River in 2023. Secondly, the construction of the Shilin Weir by the Taiwan Power Company in the upstream area of the Daan River aimed to prioritize water diversion for hydropower generation while ensuring domestic water supply for Miaoli County and Taichung City. Lastly, there was an unusual increase in the number of roadkill FFBs during the rainy season of 2023. The decreased rainfall in FFB habitats in the mountains and the near-dry condition of the upstream Daan River caused by the Shilin Weir in 2023, allowing FFBs to easily cross the Daan River into Miaoli County. The evidence of unusually increased FFB activity in 2023 supports the speculation that FFBs crossed the Daan River, introducing FFB rabies into Miaoli County.